Evolution process of the Yinduba paleolandslide-dammed lake in the upper Jinsha River, SE Tibetan Plateau - Xu, Hui; Chen, Jian; Chen, Ruichen; Cui, Zhijiu; Mi, Dongdong; Shi, Lulu (Frontiers in Earth Science, 2023)
Lacustrine terraces at Yinduba in the upper Jinsha River of SE Tibetan Plateau indicate that a large paleo-dammed lake formerly existed in this area. Based on landscape survey, optically stimulated luminescence (OSL) dating and sedimentary analyses, this research shows that the Yinduba paleolandslide-dammed lake (PDL) was formed by a catastrophic rock avalanche before 74 ka ago, with the corresponding lake depth and lake length being 110 m and 22 km, respectively. Controlled by the multi-stage breaching of the dam body, the Yinduba PDL underwent two lake level declines until its final breach after 36 ka B.P., with the life span of up to 38,000 years. During the duration, the Yinduba PDL imposed a temporary local base level of erosion, with the average downcutting rate of the landslide dam being 1.7 m/ka. This study supports the possibility of a large landslide-dammed lake having the life span of up to tens of millennia, and provides new evidence regarding the evolutionary history of a dammed lake.